Hyperledger Fabric Framework with 5G Network for Blockchain-based Security of IoT Smart Home Applications - Ali, R.F. (Institute of Electrical and Electronics Engineers Inc., 2021)
In today's world, Internet of Things (IoT) device and data security is still a significant problem. IoT devices are small and light, with little or no processing capability to run complicated and computationally intensive security algorithms. In their natural state, IoT devices are centralized and have a single point of failure. Therefore, when we exchange data, there is a chance of fake authenticity and phishing. Due to its decentralized nature and resilience, this study tries to eliminate data security problems utilizing the phenomenon known as the blockchain. The Hyperledger framework was employed for block chaining, which employs its fabrication technology for the security of IoT devices and data. We have chosen an IoT-based smart home environment to test our data security solutions because of the diversified nature of 10T devices. Â© 2021 IEEE.